2013
DOI: 10.1177/0300060513499100
|View full text |Cite
|
Sign up to set email alerts
|

Real-time imaging of cerebral infarction in rabbits using electrical impedance tomography

Abstract: Objective: To investigate the possible use of electrical impedance tomography (EIT) in monitoring focal cerebral infarction in a rabbit model. Methods: A model of focal cerebral infarction was established in eight New Zealand rabbits using a photochemical method without craniectomy. Focal cerebral infarction was confirmed by histopathological examination. Intracranial impedance variation was measured using 16 electrodes placed in a circle on the scalp. EIT images were obtained using a damped least-squares reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…The validation of this electrode configuration in detecting the intracranial impedancehas been demonstrated by the large number of animal experiments [31, 32] and clinical studies[33, 34]. At present, for brain EIT, some studies have reported that the multiple-plane electrode configuration might enhance intracranial sensitivity and improve the image reconstruction performance in detecting intracranial lesions [35, 36].…”
Section: Discussionmentioning
confidence: 99%
“…The validation of this electrode configuration in detecting the intracranial impedancehas been demonstrated by the large number of animal experiments [31, 32] and clinical studies[33, 34]. At present, for brain EIT, some studies have reported that the multiple-plane electrode configuration might enhance intracranial sensitivity and improve the image reconstruction performance in detecting intracranial lesions [35, 36].…”
Section: Discussionmentioning
confidence: 99%
“…The photothrombotic stroke method was used to establish the ischemic model [36]. Using a dental drill with a 10-mm diameter, a hole was drilled 5 mm anterior to the coronal suture and 6 mm to the left of the sagittal suture.…”
Section: Methodsmentioning
confidence: 99%
“…Wu et al established an ischemic brain model in rabbits by ligating the carotid arteries, and used two-electrode technique to measure the impedance spectra of normal and ischemic brain across the 0.1 Hz–1 MHz range [19]. Other research groups monitored changes in impedance before and after brain ischemia at a single frequency [20,21]. Nevertheless, in these studies, the measurements of impedance spectra of hemorrhagic brain were not taken.…”
Section: Introductionmentioning
confidence: 99%